The Chronological Development and Syntactic Functions of the Copular Verb 是 (Shì) in the Chinese Language (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article is devoted to the chronological development of the copular verb 是 (shì) in the Chinese language and its functional features within modern syntax. The study examines the usage of 是 as a lexical unit in ancient Chinese written monuments, its gradual transformation into a copular verb during the Middle Chinese period, and its role in contemporary Putonghua as a central grammatical element ensuring the relation between subject and predicate. Furthermore, the article highlights, through illustrative examples, the application of 是 in nominal, adjectival, and other types of sentences, analyzing step by step its semantic and syntactic transformation.